Flux and solder paste containing flux

The solder paste formulation with specific acrylic polymer, organic solvent, and amine components addresses viscosity and storage stability issues, enhancing soldering resistance and workability.

JP2025015456AActive Publication Date: 2025-01-30HERAEUS ELECTRONICS GMBH & CO KG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024109279
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-20
Filing Date
2024-07-06
Publication Date
2025-01-30
Estimated Expiration
2044-07-06

AI Technical Summary

Technical Problem

Existing solder pastes face issues with viscosity stability, storage stability in air, and soldering resistance, which affect their workability and printing suitability.

Method used

A solder paste formulation comprising 30-80% by weight of an acrylic polymer with a specific molecular weight range, 10-60% by weight of an organic solvent, 0-15% by weight of an amine, and 0-20% by weight of additional components, including a carboxylic acid or halogen compound, to enhance viscosity stability and soldering resistance.

Benefits of technology

The formulation provides improved viscosity stability, storage stability, and soldering resistance, ensuring consistent workability and printing suitability without air oxidation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015456000001
    Figure 2025015456000001
Patent Text Reader

Abstract

To provide a flux which has good viscosity and storage stability, and has good solderability in the atmosphere, a solder paste composed of the flux and a use of the same.SOLUTION: There are provided a flux which is composed of (i) 30 to 80 wt.% of one or more acidic (meth)acryl copolymers having an acid value of 100 to 350 mgKOH / g and a weight average molecular weight Mw of 1,000 to 5,000, (ii) 10 to 60 wt.% of at least one organic solvent, (iii) 0 to 15 wt.% of one or more amines, and (iv) 0 to 20 wt.% of one or more components other than the components (i) to (iii); and a solder paste which is composed of 80 to 92 wt.% of one or more different solders, and 8 to 20 wt.% of a flux.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to fluxes for solder pastes, and in particular to solder pastes containing fluxes for attaching electronic components to substrates.

[0002] Solder pastes, in particular soft solder pastes, are primarily used in the manufacture of electronic circuits to create mechanical, electrical and thermal connections between electronic components and substrates, or more precisely between the contact surfaces of the latter provided for this purpose. Summary of the Invention [Problem to be solved by the invention]

[0003] Examples of electronic components within the meaning of this patent application include diodes, LEDs (light emitting diodes), dies, IGBTs (insulated gate bipolar transistors), MOSFETs (metal oxide semiconductor field effect transistors), ICs (integrated circuits), sensors, heat sinks, resistors, capacitors, coils, connecting elements (e.g. clips), base plates, antennas, etc.

[0004] Examples of substrates within the meaning of this patent application include lead frames, PCBs (printed circuit boards), flexible electronics, ceramic substrates, metal-ceramic substrates such as DCB substrates (direct bond copper substrates), IMS (insulated metal substrates), etc.

[0005] Electronic components are typically contacted or applied to a substrate via a solder paste. The solder paste is heated to melt the solder (solder metal, solder alloy) in the paste, for example by a reflow process. After the solder cools and solidifies, the electronic component and substrate are firmly joined together.

[0006] In addition to the solder powder, solder pastes typically contain a flux, which serves, among other things, to dissolve oxide layers on the surfaces of the solder powder, electronic components and substrates, thereby improving wettability during the soldering process.

[0007] Fluxes forming part of the solder pastes are typically based on natural resins, in particular colophony, and furthermore organic solvents, buffer bases, e.g. amines, and activators, e.g. carboxylic acids or halogen compounds, are typically included as ingredients in such fluxes.

[0008] The object of the present invention is to provide a solder paste which has an improved viscosity and thus an improved storage stability, and preferably also an improved solderability in the presence of air, i.e. good solderability without the need to take additional special measures to exclude atmospheric oxygen, such as vacuum soldering or soldering under inert gas. High viscosity stability is likewise associated with consistent processability, for example in particular consistent printability.

[0009] The applicant has been able to develop a flux that solves this problem, or more precisely a solder paste that includes a flux that solves this problem. The present invention therefore relates to a flux comprising: (i) 30 to 80 wt.% (weight %), preferably 35 to 70 wt.%, of an acid value in the range of 100 to 350 mg KOH / g and a weight average molecular weight M in the range of 1000 to 5000 w one or more acidic (meth)acrylic copolymers having the formula (ii) 10 to 60% by weight, preferably 20 to 50% by weight, of at least one organic solvent, (iii) 0 to 15% by weight, preferably 4 to 12% by weight, of one or more amines; (iv) 0 to 20% by weight of one or more components other than components (i) to (iii); The object of the present invention is to provide a flux comprising:

[0010] "(Meth)acrylic" means "methacrylic" and / or "acrylic".

[0011] The term "acid number" as used in the specification and examples refers to the acid number (SZ) which can be determined in accordance with DIN EN ISO 2114 in mg KOH / g (milligrams KOH / gram).

[0012] Unless otherwise noted, all standards cited herein are the editions prevalent as of the priority date of this patent application.

[0013] The weight average molecular weight M referred to in the specification and examples w can be determined in the usual manner known to those skilled in the art by GPC, for example according to DIN 55672-1 (March 2016; crosslinked polystyrene as stationary phase, tetrahydrofuran as liquid phase, polystyrene standards, 23° C.).

[0014] Depending on the presence of components (iii) and / or (iv), the flux may consist accordingly of components (i)+(ii), or (i)+(ii)+(iii), or (i)+(ii)+(iv), or (i)+(ii)+(iii)+(iv), where in each of these alternatives the sum of the weight percent of the respective components equals 100 weight percent.

[0015] As component (i), the flux according to the invention comprises 30-80% by weight, preferably 35-70% by weight, of one or more different acidic (meth)acrylic copolymers. Preferably, there is only one acidic (meth)acrylic copolymer. The acidic (meth)acrylic copolymer has an acid number in the range of 100-350 mg KOH / g, preferably 150-300 mg KOH / g. The acidic (meth)acrylic copolymer has a weight average molecular weight M in the range of 1000-5000, preferably in the range of 1000-3000, in particular in the range of 1500-2500. w It has an acid value in the range of 150 to 300 mg KOH / g and a weight average molecular weight M in the range of 1000 to 3000 or 1500 to 2500. wPreferred are acidic (meth)acrylic copolymers having the formula: These are copolymers of (meth)acrylic compounds that can be prepared in the usual manner known to those skilled in the art by radical copolymerization, and it is also possible for the copolymers to contain comonomers other than (meth)acrylic type comonomers, such as vinyl compounds and / or other olefinically unsaturated radically copolymerizable compounds, in a total weight percentage of <50% by weight, based on the total acidic (meth)acrylic copolymer. Examples of (meth)acrylic compounds that constitute >50% by weight, based on the total (meth)acrylic copolymer, are (meth)acrylic acid, (meth)acrylic acid esters and (meth)acrylamides. Examples of vinyl compounds include compounds such as vinyl esters, vinyl ethers, styrene, etc.

[0016] The acidic (meth)acrylic copolymer has a glass transition temperature (T g The glass transition temperature can be determined using dynamic differential scanning calorimetry (DSC) according to DIN 51007 at a heating rate of 10 K / min.

[0017] Acidic (meth)acrylic copolymers of the type described above are commercially available. Examples thereof can be found under the name Indurez from Indulor Chemie GmbH and under the name Joncryl® from BASF.

[0018] As component (ii), the flux according to the invention comprises 10-60% by weight, preferably 20-50% by weight, of at least one organic solvent. Examples include diols, alcohols, ether alcohols, and ketones that are liquid at 25°C, in particular trimethylpropanol, 1,2-octanediol, 1,8-octanediol, 2,5-dimethyl-2,5-hexanediol, isobornylcyclohexanol, glycol ethers, 2-ethyl-1,3-hexanediol, n-decyl alcohol, 2-methyl-2,4-pentanediol, terpineol, and isopropanol, as well as mixtures thereof. Examples of glycol ethers include mono-, di-, and tripropylene glycol methyl ether, mono-, di-, and tripropylene glycol n-butyl ether, mono-, di-, and triethylene glycol n-butyl ether, ethylene glycol dimethyl ether, triethylene glycol methyl ether, diethylene glycol dibutyl ether, tetraethylene glycol dimethyl ether, and diethylene glycol monohexyl ether, as well as mixtures thereof.

[0019] As component (iii), the flux according to the present invention comprises 0-15 wt. %, preferably 4-12 wt. %, of one or more amines, i.e. the flux according to the present invention may or may not comprise one or more amines, preferably one or more amines. Examples of amines include N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetraethylethylenediamine, N,N,N',N'-tetrapropylethylenediamine, N-coco-1,3-diaminopropane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, and 1,10-diaminodecane, bis(2-ethylhexyl)amine, bis(2-methylhexyl)amine, diethylamine, triethylamine, cyclohexylamine, diethanolamine, triethanolamine, hydrogenated tallow alkylamines, hydrogenated (tallow alkyl) dimethylamines, and hydrogenated bis(tallow alkyl) methylamines.

[0020] As component (iv), the flux according to the invention comprises 0-20% by weight of one or more components different from components (i)-(iii), i.e. the flux according to the invention may comprise one or more type (iv) components or none. Examples of type (iv) components include in particular thickeners, but may also include activators, defoamers, wetting aids and / or stabilizers.

[0021] Examples of thickening agents include ethyl cellulose, hydrogenated castor oil, glycerol-tris-12-hydroxystearin, and modified glycerol-tris-12-hydroxystearin.

[0022] Examples of low molecular weight carboxylic acids that can be used as activators include benzilic acid, oxalic acid, adipic acid, malonic acid, succinic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid and tridecanedioic acid. It may be advantageous for the flux according to the invention to comprise 2-15% by weight of at least one low molecular weight carboxylic acid as type (iv) component. Thus, in such an embodiment, up to 5-18% by weight of further type (iv) components (but different from the low molecular weight carboxylic acid) may be included in the flux according to the invention.

[0023] Examples of halogen-containing compounds useful as activators include aniline hydrochloride, glutamic acid hydrochloride, diethanolamine hydrochloride, diethanolamine hydrobromide, triethanolamine hydrochloride, triethanolamine hydrobromide, and trans-2,3-dibromo-2-butene-1,4-diol.

[0024] Preferably, the flux according to the invention, i.e. the entire flux consisting of components (i)+(ii) or (i)+(ii)+(iii) or (i)+(ii)+(iv) or (i)+(ii)+(iii)+(iv), has a flux acid number (FMSZ) in the range of 100-250 mg KOH / g, preferably in the range of 120-220 mg KOH / g. The flux acid number referred to in the present specification and in the examples can be determined according to IPC TM-650 2.3.13 (Amendment A of date 06 / 2004). The flux acid number is at least substantially or completely formed from the carboxyl groups of component (i) and the carboxyl groups optionally provided by component (iv).

[0025] The present invention further comprises providing a solder paste comprising 80-92% by weight of one or more different solders and 8-20% by weight of a flux according to the present invention, i.e. a flux according to the present invention in one of the previous embodiments, the sum of the weight percentage of the solder according to the present invention and the weight percentage of the flux being 100% by weight.

[0026] As mentioned above, the solder paste according to the invention comprises 80-92% by weight of one or more different solders, in particular a tin-based solder (a solder alloy comprising at least 80% by weight, preferably at least 83% by weight, in particular 90-99.5% by weight of tin) or a bismuth / tin-based solder (a solder alloy comprising 50-60% by weight of bismuth and 40-50% by weight of tin).

[0027] The solder preferably has a liquidus temperature in the range of 150 to 350°C, preferably in the range of 180 to 300°C.

[0028] The solder is present in the solder paste according to the invention as solder powder, as is usual for solder pastes. The ball size of the solder balls constituting the solder powder can correspond to any of the classifications according to the IPC J-STD-005A standard, i.e. the solder paste according to the invention can have solder balls of any type ball size within the type range T1 to T7.

[0029] Preferably, the solder paste according to the invention has a viscosity of 50 to 250 Pa·s. The viscosities mentioned in the present specification and in the examples are measured at 25° C. and 10 s using a plate-plate rheometer (e.g., a plate-plate rheometer Physica MCR 150 from Anton-Paar) with a plate diameter of 50 mm and a measuring gap of 400 μm. -1 The shear rate can be determined using

[0030] A further object of the invention is a method for producing the solder paste according to the invention.

[0031] The method for producing a solder paste according to the present invention comprises the steps of: mixing the components of the flux according to the invention; and c) adding solder powder as described above.

[0032] The solder powder is preferably added in multiple portions, with stirring, to the prepared mixture of flux components according to the present invention, generally without heating.

[0033] The solder paste according to the present invention can be used to connect electronic components to a substrate, and it can also be used to produce solder deposits on a substrate.

[0034] When connecting an electronic component to a substrate, the contact surface of the substrate and the contact surface of the electronic component are joined via the solder paste according to the present invention.

[0035] A method of attaching an electronic component to a substrate using a solder paste according to the present invention comprises the steps of: a) providing an electronic component having a contact surface; b) providing a substrate having a contact surface; c) applying a solder paste to the contact surfaces of the electronic components and / or the contact surfaces of the substrate; d) bonding a contact surface of the electronic component to a contact surface of the substrate using solder paste; e) heating the solder paste above the liquidus temperature of the solder and then cooling the solder to solidify and form a strong bond between the electronic component and the substrate.

[0036] Steps a) and b) are self-explanatory and do not require further explanation.

[0037] In step c), the solder paste according to the invention may be applied to one or both contact surfaces by conventional methods known to those skilled in the art, such as screen or stencil printing, or dispensing or jetting.

[0038] In step d), the contact surfaces of the electronic component and the substrate can be joined together using a solder paste, i.e. a sandwich arrangement can be created from the electronic component and the substrate with the solder paste between their contact surfaces.

[0039] In step e) the sandwich assembly is soldered by heating the solder paste above the liquidus temperature of the solder, so that after cooling and solidification of the solder a robust connection is formed between the electronic component and the board via the solder paste. The solder paste is preferably heated in such a way that the solder goes into a liquid phase but does not damage the electronic component and / or the board. The sandwich assembly, and more precisely the solder paste, is preferably heated to a temperature between 5 and 60° C., preferably between 10 and 50° C., above the liquidus temperature of the solder.

[0040] Advantageously, a solder paste comprising a flux according to the invention allows soldering according to step e) in air, regardless of the ball size of the solder powder used in the solder paste. EXAMPLES

[0041] Flux and solder paste preparation The flux ingredients were combined according to Table 1 and homogenized.

[0042] To prepare the solder paste, 11 parts by weight of the flux were mixed with 89 parts by weight of solder powder (SnAgCu: 96.5 wt% Sn, 3.0 wt% Ag, 0.5 wt% Cu, type 4 according to IPC J-STD-005A standard) to form the solder paste.

[0043] Wetting ability under normal atmospheric conditions The wetting of the solder pastes was evaluated using the melting test according to test method 2.4.45 of IPC-TM-650 (1 / 95) under normal atmospheric conditions. For this purpose, the solder paste to be tested was applied to a copper plate (20 mm x 20 mm x 0.5 mm). If the surface of the copper plate had an oxide film, it was polished with P600 grade sandpaper to a bright metal finish and cleaned with alcohol. Copper plates with bright and clean surfaces were cleaned with alcohol only.

[0044] The prepared copper plate was printed using a stencil. To do so, the template was pressed firmly against the copper plate so that the opening of the template was centered on the copper plate. The solder paste to be tested was placed on a spatula and spread over the opening of the stencil, first with light and then with slightly stronger pressure, until there was no more solder paste on the stencil. The stencil was then carefully peeled off, retaining the pattern defined by the stencil. The printed copper plate was placed on a first 200 ° C high-temperature heating plate, set at a temperature below the liquidus temperature of the solder, for 2 minutes, and then immediately placed on a second heating plate, set at a temperature 50 ° C above the liquidus temperature of the solder. After the solder paste or solder had melted, the copper plate was left on the second heating plate for another 5 seconds, removed and cooled.

[0045] After the solder paste cooled, it was evaluated whether it melted into a spot corresponding to the size of the stencil opening or into multiple small spots, and whether the solder paste had sharp edges after melting, and whether the surface was glossy or matte.

[0046] Solder pastes were classified into four classes. Class 1: The remelted area was larger than the area previously printed with solder paste. Class 2: The remelted surface corresponded to a surface previously printed with solder paste. Class 3: The remelted area was smaller than the area previously printed with solder paste (slight solder repelling was observed). Class 4: The solder paste formed one or more solder balls and did not wet the copper plate or melt completely.

[0047] Viscosity stability test at room temperature First, the initial viscosity of the freshly prepared solder paste was measured using a plate-plate rheometer (Physica MCR 150 from Anton-Paar; plate diameter 50 mm, measurement gap 400 μm) at 25 °C and 10 s-1 The viscosity was determined at a shear rate of 100 MPa. Each solder paste was then stored in a sealed container at room temperature (23° C.) and measured again after 7 days as described above. Before measuring the viscosity after 7 days of storage, each solder paste was briefly mixed homogeneously by hand using a spatula. The difference between the first measurement recorded immediately after preparation of the corresponding solder paste and the second measurement recorded after storing the corresponding solder paste for 7 days was evaluated as follows: ++:<5Pa·s +:5Pa·s~<10Pa·s -:>10Pa·s [Table 1]

Claims

1. A flux, (i) 30 to 80% by weight of an acid number in the range of 100 to 350 mg KOH / g and a weight average molecular weight M in the range of 1000 to 5000 w and one or more acidic (meth)acrylic copolymers having the formula: (ii) 10 to 60% by weight of at least one organic solvent; (iii) 0 to 15 wt. % of one or more amines; (iv) 0 to 20% by weight of one or more components other than components (i) to (iii).

2. The acid value is in the range of 150 to 300 mg KOH / g, and the weight average molecular weight M w The flux of claim 1, wherein the Mn is in the range of 1000 to 3000.

3. The acidic (meth)acrylic copolymer has a glass transition temperature (T g 3. The flux according to claim 1 or 2, comprising:

4. The flux of any one of claims 1 to 3, wherein the flux has a flux acid number (FMSZ) in the range of 100 to 250 mg KOH / g.

5. A solder paste consisting of 80-92% by weight of one or more different solders and 8-20% by weight of the flux according to any one of claims 1 to 4.

6. 6. Use of the solder paste according to claim 5 for connecting electronic components to a substrate or for producing a solder deposit on a substrate.

Citation Information

Patent Citations

  • Flux for soldering, and soldering paste composition

    JP2005074449A

  • Solder bump formation method

    JP2012004347A

  • Resin composition for forming solder bump, method for forming solder bump, and member provided with solder bump

    JP2015042419A

  • Flux for solder paste, solder paste, method for forming solder bump using solder paste and method for manufacturing junction body

    JP2019025546A

  • Solder paste composition and solder precoating method

    US20080179383A1